Psicoanalisi del delirio - Migone, Paolo (Il sogno della farfalla, 2020)
In this article the author presents some psychoanalytic hypotheses on the psychodynamic of delusion. The article particularly describes the early Freudian contributions such as the Drafts H (Paranoia) and K (The defensive neurosis) from 1895 and the writing about the President Schreber from 1910 in which Freud identified the defensive mechanism of paranoia. The author also takes into account some more recent psychoanalytic propositions and provides some suggestions about the clinical treatment of delusional patients.